Ludicidade e imaginação no contexto escolar: novas perspectivas amparadas na sociologia da infância - Luccas, Michele Dias [UNESP]; Alves, Nathália Franco [UNESP]; Lima, José Milton de [UNESP]; Lima, Marcia Regina Canhoto de [UNESP]; Romero, Luiz Rogério [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present work exposes the project entitled "playing in the Home: A proposal for initial and recurrent Training", which has as an object of research and intervention child and playfulness, as privileged educational resource in the context of early childhood education. The theoretical references are based primarily on the Sociology of childhood and other scholars on the subject. The purpose of the project to insert the playfulness in the school, such as language that contributes to the development of imagination and motor skills, intellectual, and social ethics of children as well as raise awareness among educators about the importance of playfulness to the integral development of children. The methodology used is action research that underlies the concern of transformation of reality and the narrowing between theory and practice. It turns out that gradually, by means of interventions are occurring changes of conceptions and attitude of the participants in the treatment of playfulness as indispensable activity in the context of early childhood education.

O presente trabalho expõe o projeto intitulado “Brincando no Lar: Uma Proposta de Formação Inicial e Continuada”, que tem como objeto de pesquisa e intervenção a criança e a ludicidade, como recurso pedagógico privilegiado no contexto da Educação Infantil. Os referenciais teóricos baseiam-se principalmente em autores da Sociologia da Infância e outros estudiosos acerca da temática. A finalidade do projeto á de inserir a ludicidade no meio escolar, como linguagem que contribui para o desenvolvimento da imaginação e das habilidades motoras, intelectuais, éticas e sociais das crianças, além de sensibilizar os educadores sobre a importância da ludicidade para o desenvolvimento integral das crianças. A metodologia utilizada é a pesquisa-ação que sustenta a preocupação de transformação da realidade e o estreitamento entre a teoria e prática. Verifica-seque, gradativamente, por meio das intervenções estão ocorrendo mudanças de concepções e de posturas dos participantes no tratamento da ludicidade como atividade indispensável no contexto da Educação Infantil.
Keywords: Sociology of childhood; Early childhood education; Playfulness; Sociologia da infância; Educação infantil; Ludicidade